Probiotic characteristics of bacteriocin-producing Enterococcus faecium strains isolated from human milk and colostrum - Bagci, Ufuk; Ozmen Togay, Sine; Temiz, Ayhan; Ay, Mustafa (Folia microbiologica, 2019)
As potential probiotic traits of human milk-isolated bacteria have increasingly been recognized, this study aimed to evaluate the probiotic properties of bacteriocin-producing Enterococcus faecium strains isolated from human milk and colostrum. Among 118 human milk- and colostrum-isolated lactic cocci, only 29 were identified as Enterococcus. Of these, only four Enterococcus faecium isolates exhibited bacteriocigenic activity against several pathogenic Gram-positive bacteria, including Listeria monocytogenes. These isolates exhibited high acid (up to pH 3.0) and bile tolerance (0.5% oxgall) in simulated gastrointestinal conditions, demonstrating their ability to survive through the upper gastrointestinal tract. All of the E. faecium strains were shown to be sensitive to most of the antibiotics including vancomycin, tetracycline, rifampicin, and erythromycin, while they were resistant to kanamycin and chloramphenicol. None of the strains showed any virulence (gelE, agg2, clyA, clyB, clyM) and antibiotic resistance genes (vanA, vanB, ermB, tetM, and aac(6')-le-aph(2″)-la). In addition, all the strains were able to assimilate cholesterol, ranging between 25.2-64.1% and they exhibited variable adherence (19-36%) to Caco-2 cells. Based on the overall results of this in vitro study, four of the E. faecium strains isolated from human milk and colostrum can be considered as promising probiotic candidates; however, further in vivo evaluations are required.
Keywords: Microbial Sensitivity Tests; Gastric Juice; Cholesterol; Bile Acids and Salts; Humans; Caco-2 Cells; cholesterol; Caco-2 buňky; žlučové kyseliny a soli; mateřské mléko; Colostrum; mikrobiální testy citlivosti; Listeria monocytogenes; lidé; antibakteriální látky; Bacterial Adhesion; Antibiosis; žaludeční šťáva; bakteriální adheze; kolostrum; Milk, Human; Anti-Bacterial Agents; Enterococcus faecium; Bacteriocins; Drug Resistance, Bacterial; antibióza; probiotika; bakteriální léková rezistence; Probiotics; bakteriociny